2008
DOI: 10.1177/0961000607086618
|View full text |Cite
|
Sign up to set email alerts
|

Constructing librarians' information literacy expertise in the domain of nursing

Abstract: This article investigates negotiations of librarians' expertise in relation to information literacy at the micro-level, specifically in the domain of nursing education. A qualitative empirical framework is employed. The study draws on 18 semi-structured interviews, 16 with Swedish nursing students, one with a librarian and one with a nursing professor. Three themes on librarians' expertise emerge in the findings: technical-administrative, information searching, and source evaluation expertise. The themes have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 14 publications
3
19
0
2
Order By: Relevance
“…This presentation will take its point of departure in previous research on web‐based mediation of information literacy (Sundin, 2008) as well as nursing students' learning of information literacy (Sundin, Limberg & Lundh, 2008). Information literacy is in these studies understood in the sociocultural settings in which information artefacts are employed and in which the credibility and cognitive authority is created.…”
Section: Olof Sundin: How Can Credibility and Authority Of Informatiomentioning
confidence: 99%
“…This presentation will take its point of departure in previous research on web‐based mediation of information literacy (Sundin, 2008) as well as nursing students' learning of information literacy (Sundin, Limberg & Lundh, 2008). Information literacy is in these studies understood in the sociocultural settings in which information artefacts are employed and in which the credibility and cognitive authority is created.…”
Section: Olof Sundin: How Can Credibility and Authority Of Informatiomentioning
confidence: 99%
“…Issues of control over instructional objectives also featured in their representations. Similar findings are also borne out in interviews with librarians themselves (e.g., Julien & Pecoskie, 2009;Sundin et al, 2008). (2010) found that instructional librarians' posts about the social web on ILI-L were informed by competing impulses.…”
Section: Literature Reviewmentioning
confidence: 61%
“…This paper builds on the previous studies by analyzing the ways librarians and teachers/professors are represented across the educational spectrum in the professional LIS literature. Whereas Julien and Given (2003) and Hoffman and Polkinghorne (2010) selected listserv postings for their status as "unscripted" comments, this article will analyze published texts because these represent views that have been vetted and accepted by other members of the profession -or "community of justification" (Sundin et al, 2008) --through the publication process.…”
Section: Theoretical Approach and Methodologymentioning
confidence: 99%
“…Duncan & Holtslander, 2012;Jacobsen & Andenaes, 2011;Ragneskog & Gerdner, 2006), and collaboration between faculty and library staff is essential to succeed (Bønløkke et al, 2015;Cader et al, 2006;Gannon-Leary et al, 2003;Nayda & Rankin, 2008). The library staff has to engage in the domain of nursing to fully understand and accommodate the specific information needs of nursing students (Sundin et al, 2008). The teaching content and the learning goals should be consistent.…”
Section: Introductionmentioning
confidence: 99%